Case report and literature review: Giant retroperitoneal cystic lymphangioma - Su, Tieshan; Li, Chaoyuan; Song, Bin; Song, Defeng; Feng, Ye (Frontiers in Surgery, 2023)
Background: cystic lymphangioma is a rare benign tumor of the lymphatic system, which is most common in the neck, head and armpit, but less than 5% of lymphangiomas occur in the abdominal cavity and even less in the retroperitoneum. Case description: a 65-year-old male patient was diagnosed with "abdominal mass found for 1 year, abdominal pain, abdominal distension and dyspnea for 7 days". After abdominal CT, a giant multilobed abdominal lymphangioma was suspected, which squeezed the intestinal canal and was closely related to the inferior vena cava. The patient underwent exploratory laparotomy. During the operation, it was found that the tumor formed extensive adhesion with the transverse colon, small intestine and pelvic wall, and enveloped the abdominal aorta, superior mesenteric artery, inferior mesenteric artery and inferior vena cava to varying degrees. But we still struggled to remove the cyst completely. Postoperative pathology confirmed the diagnosis of retroperitoneal cystic lymphangioma. The patient recovered well after operation, ate normally 5 days after operation, was discharged smoothly 10 days after operation, and was followed up 1 month after operation. There was no evidence of recurrence. Conclusion: In this case, we report a patient with giant retroperitoneal cystic lymphangioma who underwent exploratory laparotomy combined with preoperative abdominal CT and acute abdominal pain, abdominal distension and dyspnea. Because of the large volume of the tumor and its close relationship with the superior mesenteric artery and other blood vessels, the surgeon used scissors to separate the tumor sharply and removed the whole tumor completely.